The influence of the COVID-19 pandemic on audit fees and audit report timeliness of listed firms in Ghana - Alhassan Musah; Bismark Okyere; Isaac Osei-Bonsu (Cogent Business & Management, 2023)
The objective of the study is to examine the effect of the COVID-19 pandemic on audit fees and delays in the release of audit reports among the publicly listed entities in Ghana. The study sampled 35 listed firms over 5 years from 2017 to 2021 by extracting data from the annual report of the firms. The study relied on a panel regression model to estimate the extent to which COVID-19 predicts changes in audit fees and audit report timeliness among listed firms in Ghana. The analysis of the results revealed a positive coefficient between COVID-19 pandemic and audit fees and the positive coefficient was also statistically significant. The study also found a positive and statistically significant association between the COVID-19 pandemic and audit report timeliness which suggest that the pandemic resulted in the delay in the release of audit report among listed entities in Ghana. The combined effect of the two key findings is that the COVID-19 pandemic had a significant influence on audit quality among listed firms in Ghana. The result has significant policy implications especially from the perspective of the Institute of Chartered Accountants Ghana in terms of drawing auditors' attention to the increased audit risk brought about as a result of the COVID-19 pandemic and the need to compensate for that with the high-quality audit.
Keywords: 650; COVID-19 pandemic; Ghana; audit fees; audit report timeliness; listed firms